Persistent Left Fifth Aortic Arch with Pentalogy of Fallot - Furtado, A. D.; Manohar, S. R. K.; Pradhan, S. K.; Pillai, V.; Karunakaran, J. (The Thoracic and Cardiovascular Surgeon, 2012)
Congenital double-lumen aortic arch resulting from persistence of the fifth aortic arterial arch (PFAA) is a rare congenital anomaly. It appears as a vascular structure running inferior and parallel to the “real” aortic arch from the innominate artery to the left subclavian artery. We report a case of persistent fifth aortic arch (systemic-to-systemic arterial connection) with pentalogy of Fallot in a patient who underwent successful intracardiac repair with a transannular patch with very proximal aortic cannulation for cardiopulmonary bypass (CPB).
Keywords: cardiac anatomy/pathologic anatomy; congenital heart disease, CHD; echocardiography (all modalities, applications); persistent fifth aortic arch; pentalogy of Fallot; intracardiac repair; aortic cannulation; CPB